Feelings or Words? Understanding the Content in Self-Report Ratings of Experienced Emotion. [article]. - Barret, Lisa F.
People differ in the extent to which their verbal reports of experienced emotion are valence focused or arousal focused. Three multimethod studies are reported to explore whether differential focus reflects individual differences in the cognitive structure of emotion language versus differences in phenomeno-logical experience. Although there was some evidence that valence focus and arousal focus were linked to variations differences in cognitive structure, the findings are also consistent with the view that self-report ratings are being driven by the properties of the feelings that are being reported. Implications for the study of experienced emotion are discussed. -- (from the author)